ANALYSIS OF FACTORS THAT OPPOSE BUSINESS DEVELOPMENT IN SMALL-SCALE FOOD AGRO-INDUSTRY - Solichin, Endang (Dinasti International Journal of Management Science, 2020)
This study aims to analyze the influence of entrepreneurial characteristics of small-scale agro-industry food business owners and the business climate created through government policy on business progress, testing and analyzing the dominant factors affecting the progress of food agro-industry on the scale of small businesses in Kediri, East Java, Indonesia.The questionnaire was designed in the form of a Likert scale with five choices, and distributed to 140 food agro-industry entrepreneurs on a small business scale in Kediri. The technical analysis uses Structural Equation Modeling (SEM) with AMOS 4 software. The results showed that the contribution of the business climate had a greater influence on business progress when compared with entrepreneurial characteristics. Based on these findings, to spur business growth and progress in small-scale agro-industry, it is necessary to have government intervention in creating a conducive business climate through advisory and assistance policies in accordance with the needs of small-scale agro-industry businesses, encouraging market creation, providing entrepreneurship training to improve the ability to manage effort.